Identification and characterization of novel anti‐tau antibodies that inhibit tau‐seed mediated pathology in a P301S tauopathy mouse model Alzheimer's Disease and tauopathies. (20th December 2022) - Liu, Wencheng; Kurella, Vinodh; Liu, Li; Kavanagh, Dillon; Paranjpe, Maneesha; Holth, Jerrah; Chung, Charlotte; Powers, Alex; Ren, Xiao‐Qin; Shu, Yanqun; Capili, Allen; Hou, Jay; et al.
Abstract: Background: The current hypothesis for the progression of tau pathology in Alzheimer's disease (AD) and tauopathies (for example, Progressive supranuclear palsy (PSP)), is based on mechanisms involving seeding and propagation of pathologic tau via cell‐to‐cell transmission, including trans‐synaptic propagation, a mechanism which provides the opportunity for anti‐tau immunotherapy as a logical and promising therapy for these diseases. Method: We have carried out parallel immunization campaigns with various immunogens and host animals aimed to isolate a diverse starting pool of anti‐tau antibodies. Immunization of mice with AD patient‐derived PHF‐tau (paired helical filamentous tau) as the immunogen yielded 113 hits demonstrating significant binding to PHF‐tau and an absence of binding to wild type recombinant tau. Result: Here, we describe the characterization of these 113 anti‐tau antibodies based on their biochemical and biophysical properties, including affinity for PHF‐tau, immunohistochemical selectivity for AD/PSP in human brain sections, functional inhibition of PHF seeding in vitro, developability, as well as epitope mapping. 10 antibodies that met the target profile described above were selected for in vivo efficacy screening in the P301S seeding‐propagation tauopathy mouse model. Epitope mapping for these 10 antibodies demonstrates that these antibodies target phospho‐tau epitopes in diverse locations throughout the tau protein, with six antibodies targeting the mid‐domain region, three targeting the C‐terminal region, and one targeting the N‐terminal/mid‐domain region. We have evaluated five antibodies for their ability to block PHF seeding/propagation in a P301S mouse seeding model and demonstrated substantial reduction of induced tau pathology. Five additional antibodies are currently under evaluation Conclusion: In summary, we have generated a set of potent and specific anti‐tau antibodies targeting a diverse set of phospho‐tau epitopes that are candidates for the treatment of Alzheimer's disease and/or other tauopathies. Both the in vitro and in vivo data on this series of tau‐specific antibodies will be presented.